1916
DOI: 10.1084/jem.24.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adult Chicken Organ Grafts on the Chick Embryo

Abstract: In the course of experiments on the factors of resistance to heteroplastic tissue grafts in the chick embryo, observations were made on the effects of certain organ grafts on the embryo itself.' The working out of the finer histological details of this process has been taken up, at my suggestion, by Dr. Vera Danchakoff. This brief note on the original observations is published now for completeness and record.Experiments.-On the 7th day of incubation openings were made in the shells of hens' eggs containing emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1924
1924
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(24 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…For example, B lymphocytes were first recognized in chickens as the antibody-producing cells and are named after the bursa of Fabricius, a gut-associated lymphoid tissue (GALT) that is required for B-cell development in chickens (1). Graft-versushost response was first described in chicken embryos (2), and the first attenuated vaccine was developed by Louis Pasteur against fowl cholera caused by Pasteurella multocida. Nevertheless, the lack of a robust genome editing technology including knockouts has put the chicken at a distinct disadvantage to mammalian species, especially the mouse, as a vertebrate animal model.…”
mentioning
confidence: 99%
“…For example, B lymphocytes were first recognized in chickens as the antibody-producing cells and are named after the bursa of Fabricius, a gut-associated lymphoid tissue (GALT) that is required for B-cell development in chickens (1). Graft-versushost response was first described in chicken embryos (2), and the first attenuated vaccine was developed by Louis Pasteur against fowl cholera caused by Pasteurella multocida. Nevertheless, the lack of a robust genome editing technology including knockouts has put the chicken at a distinct disadvantage to mammalian species, especially the mouse, as a vertebrate animal model.…”
mentioning
confidence: 99%
“…Moreover, there is no rejection of the transplantation because the immune system is not yet functional in 9-day-old chick embryos. Thus, Murphy (1916) used the chorioallantoic membrane as a host organ for tissue transplantation and investigated various chicken tissues grafted on this membrane. Katoh et al (2001) also transplanted liver pieces of the chick embryos onto the chorioallantoic membrane and showed that the liver was able to regenerate on this membrane.…”
Section: Histological Observationsmentioning
confidence: 99%
“…The chorioallantoic membrane (CAM) of the chicken embryo has been widely used for cultivating various organs and tissues, because the mesodermal layer of the membrane is rich in blood vessels to supply implants with nutrients and oxygen [Murphy, 1916;Willier, 1924;Hoadley, 1925;Willier and Rawles, 1931a, b;Sandstrom, 1934;Nakada et al, 1998a, b]. Our previous studies clearly showed that breast muscle tissues from chicken embryos totally degenerated on CAM and then regenerated by proliferation and differentiation of surviving satellite cells, muscle stem cells which are ordinarily dormant but activated by injury [Nakada et al, 1998a, b].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the liver, the early hepatic rudiment differentiated into normal liver tissues when grafted on CAM [Hoadley, 1925;Willier and Rawles, 1931a, b;Sandstrom, 1934]. On the other hand, liver tissues from newly hatched or adult chickens could not grow and degenerated on CAM [Murphy, 1916;Willier, 1924]. However, no study has been devoted to investigating regeneration of liver tissues from chicken embryos older than 6 days and the process of reconstruction of liver tissues on CAM has not been well clarified.…”
Section: Introductionmentioning
confidence: 99%